Human Trafficking in The Digital Era Through The 4Sale App in Kuwait - Alya Anaqi Putri; Arie Kusuma Paksi (Poltanesa, 2025)
This study examines how digital technology functions as an infrastructure of exploitation within the context of human trafficking, focusing on the 4Sale app in Kuwait. Initially designed as a digital marketplace for buying and selling goods, the platform has been misused to facilitate the trade of domestic workers and migrant labourers, reflecting how the commodification of human labour extends into the digital sphere. The central research question explores what factors enable digital platforms to become mediums for human trafficking and how such mechanisms are normalized within everyday online transactions. Drawing on the framework of the digital political economy, this research argues that these exploitative practices stem from the logic of digital capitalism, which prioritizes efficiency, data circulation, and profit maximization over ethical and humanitarian considerations. The study employs a qualitative approach using case analysis and secondary data from credible sources such as BBC Arabic, Europol, and the European Center for Democracy and Human Rights (ECDHR). The findings reveal that digital human trafficking is sustained by interrelated factors including technological architectures that accelerate transactions while concealing identities, structural ties between platforms and global markets that commodify human ;abour, and weak legal as well as social accountability of technology companies. Ultimately, the study concludes that digital technology operates not as a neutral tool but as a political–economic arena that amplifies the possibilities of human exploitation in the globalized era, urging stronger regulatory and ethical frameworks to govern digital platforms.